Investigation of the Mechanisms of Biocorrosion in Shipwrecks and Simulated Oilfields by Micro-Computed Tomography Analysis - Albahri, Mohammed Bassil Ali Ghalib (Curtin University, 2022)
The composition, structures, and distribution of corrosion products on metal surfaces are important factors in interpreting the corrosion process. This thesis is aimed to develop the current knowledge regarding the mechanisms of biocorrosion, by means of characterization of corrosion products formed in two distinct types of media, being: deep-sea water and simulated oilfields environments, applying a novel approach that combines X-ray micro-computed tomography (3D-scanning), with chemical, and surface analytical techniques (XRD,FTIR, Raman, and SEM-EDS analysis).